Decision making style and investment success of retail investors: the case in Sabah - Amer Azlan Abdul Jamal; Wijaya Kamal Ramlan; Khairul Hanim Pazim; Dayang Safrina Ag. Budin (Universiti Malaysia Sabah, 2014)
Since the past three decades, numerous contributions have been made by the traditional finance proponents in assisting investors making good investment decisions assuming that they are rational decision makers, and unbiased in predicting the future. Nevertheless, proponents of behavioural finance always argued that people do act in irrational manner and often make predictable errors in their forecasts thus violated these assumptions. Market anomalies and crashes are some of the examples that explain the existence of psychological bias that lead to inefficient outcomes. When come to investing, different investors would have different investment style and strategy, depending on their objectives.